Corporate Criminal Liability for Illegal Toxic and Hazardous Waste Dumping - Tofik Chandra; Bobur Sobirov (Lex Publica, 2023)
Abstract. Modern corporations and industries play a crucial role in global economic development. However, with rapid industrial growth, large-scale production, and intensive use of natural resources, humans have inadvertently created serious threats to the environmental balance. One of the most significant and damaging negative impacts is environmental pollution, specifically the problem of toxic hazardous material waste. The protection of communities from environmental crimes involves imposing criminal sanctions not only on individual legal subjects but also on corporate legal entities, a concept known as corporate criminal liability. The aim of this research is to analyze the manifestation of corporate criminal liability in cases involving the illegal disposal of hazardous toxic waste into the environment. Additionally, it seeks to examine the enforcement of corporate law in these instances. This research employs qualitative methods with a normative juridical approach. The legal sources used in this normative research include primary legal materials, secondary legal materials, and tertiary legal materials. The findings of this research suggest that the handling of corporate criminal acts, particularly in cases of hazardous toxic waste dumping, falls short of delivering complete justice due to obstacles in the investigation, prosecution, and the establishment of environmental impacts in the prosecution of corporate environmental crimes. Therefore, it is essential to consider the application of the doctrine of strict liability in cases of environmental pollution, especially in waste dumping incidents. The implementation of strict liability for corporations in the prosecution of environmental criminal acts, such as the dumping of toxic hazardous waste, eliminates the need to prove wrongdoing, whether intentional or negligent, including the motive behind the corporation’s actions. Keywords: Law, Corporation, Dumping, Waste, Toxic Hazardous Materials, Environment Abstrak. Perusahaan dan industri modern memainkan peran penting dalam pembangunan ekonomi global. Namun, dengan pertumbuhan industri yang pesat, produksi skala besar, dan penggunaan sumber daya alam yang intensif, manusia secara tidak sengaja telah menimbulkan ancaman serius terhadap keseimbangan lingkungan. Salah satu dampak negatif yang paling besar dan merusak adalah pencemaran lingkungan, khususnya masalah limbah bahan beracun dan berbahaya. Perlindungan masyarakat dari kejahatan lingkungan hidup meliputi pemberian sanksi pidana tidak hanya terhadap subjek hukum perseorangan tetapi juga terhadap badan hukum korporasi, suatu konsep yang dikenal dengan pertanggungjawaban pidana korporasi. Penelitian ini bertujuan untuk menganalisis wujud pertanggungjawaban pidana korporasi dalam kasus pembuangan limbah bahan beracun berbahaya ke lingkungan secara tidak sah. Selain itu, penelitian ini berupaya untuk memeriksa penegakan hukum perusahaan dalam kasus-kasus ini. Penelitian ini menggunakan metode kualitatif dengan pendekatan yuridis normatif. Sumber hukum yang digunakan dalam penelitian normatif ini meliputi bahan hukum primer, bahan hukum sekunder, dan bahan hukum tersier. Temuan penelitian ini menunjukkan bahwa penanganan tindak pidana korporasi, khususnya kasus pembuangan limbah B3, belum memberikan keadilan yang utuh karena adanya kendala dalam penyidikan, penuntutan, dan penetapan dampak lingkungan hidup dalam penuntutan tindak pidana korporasi. kejahatan. Oleh karena itu, penting untuk mempertimbangkan penerapan doktrin pertanggungjawaban ketat dalam kasus pencemaran lingkungan, khususnya pada insiden pembuangan limbah. Penerapan tanggung jawab yang ketat bagi korporasi dalam penuntutan tindak pidana lingkungan hidup, seperti pembuangan limbah beracun dan berbahaya, menghilangkan kebutuhan untuk membuktikan kesalahan, baik disengaja maupun lalai, termasuk motif di balik tindakan korporasi. Kata kunci: Hukum, Korporasi, Dumping, Limbah, Bahan Beracun Berbahaya, Lingkungan Hidup